Developing guidelines for interventions to reduce risk of low-speed vehicle run-overs of young children. (1st March 2011) - Armstrong, K; Obst, P; Davey, J; Thunström, H
Abstract : In Australia, research suggests that up one quarter of child pedestrian hospitalisations result from driveway run-over incidents, with the parent or family member of the child being most likely the driver of the vehicle at the time of the incident. As such, driveway run-over incidents are an important issue that need to be addressed through public health educative initiatives. A series of qualitative interviews were conducted in order to assess general behavioural and environmental changes that parents/carers had specifically undertaken in order to reduce the risk of injury to any child in their care. A second phase of the interviews was also conducted and focused on parent/carers perceptions and attitudes of the risk of a child in their care being involved in a driveway run-over incident. The interviews elicited three main themes which together built a robust model representing the main aspects parents take into consideration in making a judgement concerning the safety of their child. The first aspect concerned the safety of the domestic environment. The second aspect concerned the level of supervision a child received, whereas the third included the child's ability to understand and comply with rules, as well as maturity of risk perception and skills. The model developed from this research has direct applicability for the development and promotion of an effective intervention in order to reduce the risk of a driveway run-over incident occurring.